ANALISIS PERPUTARAN KAS, PERPUTARAN PIUTANG, DAN PERPUTARAN PERSEDIAAN DALAM MENILAI PROFITABILITAS PADA CV. BINA ZHINOFA JAYA KAB. KEDIRI - Puji Lestary; Khasanah Sahara; Puji Rahayu (Cahaya Ilmu Bangsa, 2024)
A high level of profitability in a company can be used to support the company's operational activities optimally. And the level of profitability that increases or decreases in a company can be affected by the cash turnover, receivables and inventory owned by the company. Therefore, the purpose of this study is to determine the results of the analysis of cash turnover, receivables turnover, and inventory turnover in assessing profitability at CV. Bina Zhinofa Jaya. This type of research uses quantitative descriptive research because it describes the actual state of the research object based on facts obtained during the research process. The data sources in this study use primary data and secondary data. The analysis technique used is quantitative descriptive by calculating the cash turnover ratio using the division of sales by the average cash, calculating the receivables turnover ratio using the division of sales by the average receivables, calculating the inventory turnover ratio using the division of cost of goods sold by the average inventory, and calculating the profitability ratio using the division of net profit after tax by total assets. The results of this study are cash turnover in assessing the profitability of CV. Bina Zhinofa Jaya for the 2018-2021 period, namely being able to contribute 0.74, receivables turnover in assessing the profitability of CV. Bina Zhinofa Jaya for the 2018-2021 period, namely being able to contribute 0.19, inventory turnover in assessing the profitability of CV. Bina Zhinofa Jaya for the 2018-2021 period, namely being able to contribute 2.04 and the rest is influenced by other factors that are not examined in this study.